A 1-year prospective, open-label, single-arm, multicenter, phase 3 trial of the contraceptive efficacy and safety of the oral progestin-only pill drospirenone 4 mg using a 24/4-day regimen - Thomas Kimble; Anne E. Burke; Kurt T. Barnhart; David F. Archer; Enrico Colli; Carolyn L. Westhoff (Elsevier, 2020)
Objectives: To evaluate contraceptive effectiveness and safety of oral drospirenone 4 mg 24/4-day regimen in the United States. Study design: We performed a prospective, single-arm, multicenter phase 3 trial in sexually active women for up to thirteen 28-day treatment cycles. Primary outcome was the Pearl index, calculated using confirmed on-drug pregnancies and evaluable cycles in nonbreastfeeding women aged ≤35 years. We assessed adverse events (AEs), including hyperkalemia and venous thromboembolism. Results: Of 1006 women who received at least one dose of drospirenone, 352 women (35.0%) completed the trial and 654 (65.0%) women discontinued before trial end. Most participants (92.2%) were ≤35 years; one third had a body mass index (BMI) ≥30 kg/m2. Among nonbreastfeeding women aged ≤35 years, there were 17 pregnancies (Pearl index: 4.0; 95% confidence interval [CI], 2.3-6.4; n = 953), of which three were unconfirmed and two were from sites excluded from the main analysis for major breaches of Food and Drug Administration regulations. The Pearl index was 2.9 (95% CI: 1.5-5.1) for confirmed pregnancies among 915 nonbreastfeeding women aged ≤35 years from sites with no protocol violations. Nearly all (95.4%) treatment-emergent AEs were mild or moderate in intensity. No cases of venous thromboembolism were reported. The frequency of hyperkalemia was 0.5%. Women with baseline systolic/diastolic blood pressure ≥ 130/85 mmHg had a mean reduction from baseline in blood pressure at exit visit (−8.5/−4.9 mmHg; n = 119). No other clinically relevant changes were observed. Participant satisfaction was high. Conclusion: Drospirenone 4 mg 24/4 regimen provides effective contraception with a good safety/tolerability profile in a broad group of women, including overweight or obese women. Implications: This new progestin-only contraceptive, drospirenone 4 mg in a 24/4 regimen, provides a contraceptive option for the majority of women regardless of blood pressure or BMI.